Workshop On English Speech For Islamic Boarding School Students - Angga Taufan Dayu; Nurhasanah Nurhasanah; Neneng Islamiah; Yudha Aprizani; Dewi Rosaria (Comment: an International Journal of Community Development, 2019)
The objectives of the program were to rise student’s English speech and the students can arrange the speech script. The program conducted at Babusalam boarding school Kabupaten Kapuas.It conducted in three times for giving training to the students. Direct method, demonstration and workshop were used as training method in this workshop. The instructur gave the students materials how to speech English well. After having workshop the students get new motivation in learning it. The training methods were useful to give them trainee although they are basic level . The result indicated most of students interesting to speech practice. They brave to show their speech one by one in front of instructurs.